БАЛА ҲУҚЫҚЛАРЫ - ХАЛЫҚ АРАЛЫҚ ҲҮЖЖЕТЛЕРДЕ - Қаллибеков, Т. (SCIENCE and SOCIETY, 2020)
The article examines the provisions of the Universal Declaration of Human Rights, the International Covenants on Economic, Social and Cultural Rights, the International Covenants on Civil and Political Rights, and the UN Optional Protocol. The article also emphasizes the obligations of the States parties to the Covenant to protect the rights of the child.